The Effect of Spirituality on Intention to do Corporate Social Responsibility (Economic Education Analysis Journal, 2022)
The purpose of this study was to examine the effect of spirituality on the intention to do corporate social responsibility (CSR). This study used a survey method and participants were the owner, manager, or one of the decision-makers in a printing company in Indonesia. The number of respondents was 47 from 38 printing companies in Indonesia. The analytical method used regression analysis. The test results showed that when the five dimensions of the independent variables were tested together, it can be concluded that spirituality affected the intention to do CSR. The independent variable in this study, namely spirituality had five dimensions, namely self-awareness, the importance of spiritual beliefs in life, spiritual practice, spiritual needs, and spiritual definition and the impact of spirituality. When tested per dimension, the results obtained that the dimension of self-awareness and the dimension of spiritual needs were two dimensions that had a relationship or correlation with the intention to carry out CSR, while the dimension of the importance of spiritual beliefs in life and the dimension of spiritual practice had no relationship or correlation with the intention to do CSR. The findings of this study expand accounting research, especially regarding spirituality and CSR.